Nucleation and early stages of layer-by-layer growth of metal organic frameworks on surfaces - Summerfield, Alex; Cebula, Izabela; Schröder, Martin; Beton, Peter H. (American Chemical Society, 2015)
High resolution atomic force microscopy (AFM) is used to resolve the evolution of crystallites of a metal organic framework (HKUST-1) grown on Au(111) using a liquid-phase layer-by-layer methodology. The nucleation and faceting of individual crystallites is followed by repeatedly imaging the same submicron region after each cycle of growth and we find that the growing surface is terminated by {111} facets leading to the formation of pyramidal nanostructures for [100] oriented crystallites, and triangular [111] islands with typical lateral dimensions of tens of nanometres. AFM images reveal that crystallites can grow by 5−10 layers in each cycle. The growth rate depends on crystallographic orientation and the morphology of the gold substrate, and we demonstrate that under these conditions the growth is nanocrystalline with a morphology determined by the minimum energy surface.